G141(P) Authority gradients in paediatrics – are paediatric consultants more likely to use informal address and what is the impact on team hierarchy?. (27th April 2016) - Mitchell, HK; Fulton, A; Fertleman, MB; Fertleman, CR
Abstract : Introduction: Research in the aviation industry has shown that domineering leadership leads to accidents as junior pilots are reluctant to voice their concerns about safety problems. A solution to rebalance the 'authority gradient' was to improve communication. Medicine has a clearly defined hierarchy, often demonstrated in the use of formal address towards consultants. As in aviation, there are potential implications for patient safety if junior doctors feel unable to question or challenge seniors. It may also be detrimental to training. We investigate whether formal address towards consultants is used less frequently in Paediatrics and consider whether this has any effect on authority gradient. Methods: Using a web based survey, we questioned foundation (FY) trainees at two London hospitals about how they addressed their seniors in different posts. We sought their opinions regarding use of informal address with consultants and gathered information about appropriateness, approachability and training. We compared specialty, grade and hospital. Results: We recorded information about 93 FY1 and 45 FY2 training posts. In paediatric posts all trainees used their consultant's first name, compared to 19% in other specialties. Only 3% of surgical foundation doctors used first names. Foundation trainees in paediatric posts reported they felt it was appropriate to call consultants by their first name. 75% felt either comfortable or very comfortable contacting their consultant if they made a mistake. All felt comfortable approaching their consultant with clinical queries. Paediatric foundation doctors said that it was "a very friendly and collaborative firm. Consultants were very approachable and I felt this led to better patient care." They also commented it "felt weird calling consultants by first names at first, but made them more friendly in the long run." Conclusion: Use of informal address can improve communication between junior and senior colleagues, and reduce the authority gradient. This is particularly evident in paediatrics, with improved team atmosphere reported. An area for further research is whether this has any impact on medical errors and patient safety.